Belajar Bahasa Jepang Melalui Manga: Fokus pada Pemerolehan Onomatope - Idrus, Idrus (NAWA: Journal of Japanese Studies, 2024)
Mastering vocabulary is crucial to learning foreign languages, which is also true for Japanese. One of the many ways to acquire Japanese vocabulary is through various media, such as manga. Manga is rich in onomatopoeias, a valuable tool for enhancing one's grasp of Japanese vocabulary. Onomatopoeias are imitations of sounds that help convey a particular state or condition, allowing the reader or listener to imagine and even "hear" the sound effect vividly. In his work, Ono (2007) defines onomatopoeia as words outside human speech tools, words that originate from human speech tools but cannot be parsed, and words that describe situations without a voice or audibility. This study explores how manga can bolster Japanese language skills, particularly in mastering onomatopoeia as a category of Japanese vocabulary. Employing qualitative methods, the study centred on the language phenomena found in manga. Data was gathered by systematically reading manga and identifying onomatopoeias, which were then analysed to comprehend their role in enriching Japanese vocabulary acquisition. The findings underscore how manga can enhance Japanese vocabulary, mainly through its use of onomatopoeia, with accompanying images making comprehension more accessible.